The Effect Of Environmental, Social, And Governance (ESG) Score On Firm’s Bankruptcy Risk - Gustian Wiwaha; Zuliani Dalimunthe (UNIVED Press, 2025)
Avoiding bankruptcy is vital for corporate risk management and governance, impacting both companies and stakeholders. This study analyzes the effect of Environmental, Social, and Governance (ESG) practices on bankruptcy risk in G20 countries (2016–2023). Using panel data regression analysis, results indicate that strong ESG performance significantly reduces bankruptcy risk, as evidenced by higher Altman Z-Scores. Among the three pillars, the social dimension has the most substantial impact, with initiatives focused on employee welfare and community engagement enhancing operational stability. The study also finds ESG practices more effective in top carbon-emitting countries (China, the U.S., India, Russia, Japan) due to stronger stakeholder demands and access to sustainability investments, whereas other nations face challenges like limited ESG funding and weaker stakeholder pressures.